Ethnoecological, Elemental, and Phytochemical Evaluation of Five Plant Species of Lamiaceae in Peshawar, Pakistan. (27th August 2020) - Sulaiman,; Shah, S. M.; Sadaf,; Amin, M.; Gul, B.; Begum, M.
Abstract : The use of medicinal plants as an unconventional health treatment is gaining considerable recognition and popularity worldwide. The current study was designed to inspect five medicinally important species (such as Mentha longifolia (L.) Huds., Mentha piperita L., Mentha spicata L., Ocimum basilicum L., and Rosmarinus officinalis L.) of Lamiaceae, collected from district Peshawar, through ethnoecological, phytochemical, and elemental analyses. Biological spectra expressed that therophytes (60%) were the dominant life-form class, while nanophyll (60%) was the leading class among leaf size. The ethnobotanical profile showed that all the species were medicinal and ornamental (100%) each, while 60% were used in spices. Quantitative analysis for the macro- and microminerals confirmed the presence of 13 elements (C, N, O, Mg, K, P, S, Ca, Al, Si, Fe, Cl, and Na), which were present in varying amounts from species to species. The methanol extract of leaf samples was used for the analysis of phytochemical constituents such as saponins, flavonoids, tannins, terpenoids, phlobatannins, steroids, and anthraquinones. The medicinal potential of these plants was correlated with the presence of these phytochemicals. Due to the presence of active constituents, the plants had high potential in antifungal, antidiuretic, antioxidant, and anti-inflammatory activities.